Arransemen Lagu Anak Sekolah - Natasha Amalia Putri; Harisnal Hadi (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
School children's songs are Indonesian pop songs created by Oddie Agam which contain love stories during school. The aim of this work is to create a work in the form of school music. In this work, the arranger works on school children's songs in the form of school music and then combines them with a touch of drumband to form a new arrangement to be performed. The nuance of the arrangement will be packaged cheerfully and cheerfully. This "school child" work is an expression of the author's self in a form that is realized in 3 parts, based on the development of the "school child" song and the session percussion pattern, which appears in a series of rhythms and sentences using the composition techniques that have been created. as a binder for this work.